2014
DOI: 10.1016/j.neuro.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms underlying increased anxiety after soman exposure: Reduced GABAergic inhibition in the basolateral amygdala

Abstract: The recent sarin attack in Syria killed 1,429 people, including 426 children, and left countless more to deal with the health consequences of the exposure. Prior to the Syrian chemical assault, nerve agent attacks in Japan left many victims suffering from neuropsychiatric illnesses, particularly anxiety disorders, more than a decade later. Uncovering the neuro-pathophysiological mechanisms underlying the development of anxiety after nerve agent exposure is necessary for successful treatment. Anxiety is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
(130 reference statements)
2
35
0
Order By: Relevance
“…Indeed, by using microdialysis we found increased extracellular glutamate levels in the mPFC of MAGLÀ/À mice, and this observation provided direct evidence of increased of excitatory drive in the PFCpyramidal circuitry. Also alterations in GABAergic transmission in the amygdala play a key role in the etiology of anxiety-like behaviors (Prager et al 2014) and, indeed, animal models of anxiety show increased VGAT expression (Inta et al 2012). Accordingly, we observed a significant increase in VGAT immunodensity in the BLA.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Indeed, by using microdialysis we found increased extracellular glutamate levels in the mPFC of MAGLÀ/À mice, and this observation provided direct evidence of increased of excitatory drive in the PFCpyramidal circuitry. Also alterations in GABAergic transmission in the amygdala play a key role in the etiology of anxiety-like behaviors (Prager et al 2014) and, indeed, animal models of anxiety show increased VGAT expression (Inta et al 2012). Accordingly, we observed a significant increase in VGAT immunodensity in the BLA.…”
Section: Discussionsupporting
confidence: 58%
“…Impairment of CB 1 R signaling affects the neuronal excitatory/inhibitory balance with effects on emotional function and anxiety-or depressive-like behaviors (Chiba et al 2012;den Boon et al 2014;Prager et al 2014). Anxiety can be modulated by eCB in a bimodal way through the activation of different subsets of CB 1 R at excitatory/ VGluT1-or inhibitory/VGAT-positive inputs (Ruehle et al 2012), which, in turn, can affect the VGluT1 or VGAT presynaptic density and their vesicular quantal size (Daniels et al 2004;Wilson et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GABAergic control of the excitability of the BLA network appears to be particularly powerful (Rainnie, 1999;Muller et al, 2005;Pan et al, 2009;Popescu and Pare, 2011), and we have shown previously that it is severely compromised after exposure to soman (Prager et al, 2014b), along with an increase in anxiety-like behavior (Prager et al, 2014a). Therefore, in the present study, we compared the efficacy of the anticonvulsant treatments in preventing the decrease in spontaneous inhibitory activity caused by soman exposure.…”
Section: Resultsmentioning
confidence: 88%
“…It decreases neuronal excitability in the brain and plays an important role in muscle tone regulation 1. It is produced by cells in the nervous system known as GABAergic neurons that have an inhibitory action at receptors in an adult human or animal 2,3. In addition to inhibition, some GABAergic neurons, such as chandelier cells, are also capable of exciting their glutamatergic counterparts 4.…”
mentioning
confidence: 99%